We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
6
0
avatar

Hello,

Question I solved but there is not a model answer for it..

So just wanted to make sure it is correct.

L+M=9 , M-L= -6 , So, L^2 -M^2 =.....

 

 

My solution:

M-L=-6 (Multiply all with -1)

-M+L=6

(changing positions)

L-M=6 

Since, L^2 - M^2 (Different between 2 square) = (L-M) (L+M)

Therefore, 6*9 = 54.

So it is a choice question

here are all the choices:

14

-14

54

-54

 Apr 30, 2019

24 Online Users

avatar
avatar
avatar